Windows containers for IT pros : transitioning existing applications to containers for on-premises, cloud, or hybrid - Ramos Apolinario, Vinicius (Apress, 2021)
This book has everything you need to know about Windows Containers, from an IT pro and ops perspective. Containers are the next big thing in IT infrastructure. More and more, we see companies relying on Kubernetes implementations to run their workloads on-premises, in the cloud, or even in hybrid deployments. IT pros and ops teams are now faced with the challenge of getting up to speed on container architecture, knowing how it differs from virtual machines (VMs), and the best means and practices for managing their applications in containers. Windows Containers for IT Pros explores all of that, from the IT pro experience. You will approach learning about containers through the optics of an author who is accustomed to deploying virtual machines (VMs). You will learn about differences, parallel practices, use cases, and how to get started and go deep into day 2 operations. What You Will Learn: Architect and deploy Windows Containers leveraging existing skills Containerize existing applications Know best practices for managing resources in Windows Containers Get comfortable moving containers to the cloud with Azure Understand the options for using containers on Azure This book is for Windows IT pros and technical professionals deploying Windows Server and server applications today, such as .NET, ASP.NET, IIS, and more. This book assumes little to no experience with scripting as readers deploy their workloads via one of the Windows UIs (Hyper-V, Server Manager, Windows Admin Center, etc.). Knowledge of VMs and infrastructure, such as clustered operating systems, is recommended but not required. Vinicius Ramos Apolinario is Senior Program Manager on the Windows Container Platform team at Microsoft that builds the container platform that runs on Windows Server and Azure. He has been a Microsoft professional for most of his career and holds multiple certifications from Microsoft, VMware, Exin, and others. Vinicius is passionate about passing on his knowledge and contributes to the community via blogs, events, and articles. He is a published author who is regularly seen out in the community or at trade events presenting on various topics.